2020
DOI: 10.1088/1742-6596/1683/3/032009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of electric arc motion in external constant magnetic field

Abstract: The paper generalizes to the three-dimensional case the previously proposed two-dimensional mathematical model of the motion of a plasma formation in a constant transverse magnetic field. The complete system of single-fluid magnetogasdynamic approximation of the equations of the hydrodynamic method for plasma description under conditions of local thermodynamic equilibrium is simplified in the electromagnetic part. Instead of solving the complete system of Maxwell’s equations, Ohm’s integral law is applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…They found that intense turbulence is generated at the top of the electrodes during the arc burning process. Additionally, through simulation experiments on the structural model of the arc extinguishing chamber, they obtained data that are helpful for optimizing the design of circuit breaker arc extinguishing chambers [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that intense turbulence is generated at the top of the electrodes during the arc burning process. Additionally, through simulation experiments on the structural model of the arc extinguishing chamber, they obtained data that are helpful for optimizing the design of circuit breaker arc extinguishing chambers [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted by scientific research institutions such as the China Electric Power Research Institute, Beijing Jiaotong University, North China Electric Power University, and Shenyang University of Technology on the breakdown and recovery characteristics of insulation materials in circuit breakers [25][26][27][28][29][30]. The focus of the research has been the low-current cutoff of capacitor bank switches, the expected breaking characteristics of 10 kV rapid circuit breakers, and the pre-breakdown characteristics of 500 kV GIS circuit breakers.…”
Section: Introductionmentioning
confidence: 99%